Efficacy, Safety, and Overall Quality of Life of Endoscopic Submucosal Dissection for Early Colorectal Cancer in Elderly Patients - Liang Liu; Xingjie Shen; Jingyu Zhu (Gastroenterology Research and Practice)
Purpose. Studies reporting the treatment of early colorectal cancer (ECC) by endoscopic submucosal dissection (ESD) in elderly patients are lacking in China. The aim was to evaluate the efficacy, safety and overall quality of life of elderly patients with ECC who undergoing ESD. Methods. Three hundred and seventy-nine patients with 401 colorectal lesions entered into our study from March 2013 to March 2016 (Patients with an age 70 years old or older were divided into the elderly group and those who were less than 70-year-old entered the non-elderly group). Results. No significant differences were found in sex ratio, body mass index, location, endoscopic classification, pathological pattern, lesion size, mean procedure time, hospitalization days, complete excision, and en bloc resection rate between the two groups (P>0.05). No significant differences were observed between the groups in terms of complications during and after ESD procedure (P>0.05). There were no statistical differences between two groups in Quality of life index (QL-Index) and European Organization for Research and Treatment quality of life version 3.0 questionnaire (EORTC QLQ-C30) scores (P>0.05). Conclusion. ESD was relatively safe and effective for elderly patients with ECC, and it may be an recommended first-line treatment.